Diagnostic value of the basic erosive wear examination for the assessment of dental erosion on patients, dental photographs, and dental casts - Wohlrab, Theresa Friederike; Krisam, Johannes; Frese, Cornelia (Operative dentistry, 2019)
Clinical Relevance: The assessment of the basic erosive wear examination (BEWE) on patients and on dental photographs seems to yield comparable results and therefore may be a suitable tool for longitudinal monitoring of dental erosion. The assessment of BEWE on dental casts may better be used for laboratory techniques.